Procrastination and risky health behaviors: a possible way to nurture health promotion among young adults in Italy - Licata, Francesca; Citrino, Emma Antonia; Maruca, Riccardo; Di Gennaro, Gianfranco; Bianco, Aida (Frontiers in Public Health, 2024)
Background The study’s main objectives were to evaluate the distribution of levels of procrastination and its relationship with sleep quality, smoking status, alcohol consumption, and skipping breakfast, as a proxy measure of an unhealthy dietary pattern, among Italian university students. Methods A cross-sectional study was conducted at the “Magna Græcia” University of Catanzaro in the Southern part of Italy, using stratified random sampling techniques. Eligible students were sent an anonymous online survey aimed at assessing sociodemographic characteristics, procrastination levels using the Pure Procrastination Scale, sleep quality using Pittsburgh Sleep Quality Index, smoking status, alcohol consumption using WHO’s Alcohol Use Disorders Identification Tool, and breakfast habits. Results The study included 518 participants with a mean age of 23 year. More than half of the sample was enrolled in medicine or life science majors and the procrastination mean score was 15 (±5.9 SD). Being procrastinators was significantly more frequently among students who were poor sleepers, hazardous alcohol consumers and breakfast skippers. When analyzing the clustering of risky behaviors, it was found that as the number of risky behaviors increased, the procrastination score exhibited an exponential increase. Conclusion The study findings showed that university students who engage in procrastination tend to adopt risky health behaviors. The data gathered could be useful to derive targeted interventions aimed at groups more exposed to harmful health behaviors and to encourage institutional policies to promote healthy lifestyles within universities. Universities can act as hubs for cultivating a culture of well-being and promoting a healthy environment.